Development of an ultrasonic sensing technique to measure lubricant viscosity in engine journal bearing in-situ - Schirru, Michele (Springer, 2017)
This thesis presents a novel ultrasonic instrument for non-invasive and in-situ characterization of journal bearing lubricant viscosity. In particular, the application to journal bearings is described by non-invasively measuring the viscosity and localized power losses throughout operation. This ultrasonic viscometer is based on the reflection of polarized shear waves from a thin resonating coating layer to increase the measurement sensitivity, in comparison to conventional ultrasonic methods. This instrument allows for a full engine oil viscoelastic characterization in-situ. The book investigates the effects of temperature, pressure and shear rate, and describes in detail the ultrasonic setup and method. Further, it demonstrates that the same technique can be applied similarly to monitor the lubrication of other engine components. As such, it offers a unique instrument that can drive the research of oil formulations to improve engine performance and fulfill the requirements of international fuel economy regulations.
"Doctoral thesis accepted by the University of Sheffield, UK."
Keywords: Lubricating oils -- Viscosity.; Ultrasonic testing.; elektronické knihy; electronic books